The Empowerment of Village Unit Cooperation for Rejuvenation of Oil Palm Plantation in Dharmasraya Regency, West Sumatera Province - Melinda Noer; Ira Wahyuni Syarfi; Rafnel Azhari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2018)
The cooperation has long been a pillar of the national economy in Indonesia, especially in developing the economy in rural areas. The Village Unit Cooperation (KUD) was developed to accelerate agricultural development, aimed at improving the farmers 'and peasants' farming in rural areas. KUD has also assisted in the success of regional development programs based on the agricultural sector, one of the plantation sub-sector, which is a partner of the plasma of palm oil farmer group of People’s Core Plantation (PIR) program throughout Indonesia. In the province of West Sumatra, the PIR of palm oil plantations began in the 1980s as a base of regional development, and now the age of harvest has made the age of plants unproductive. Accordingly, KUD Bukit Jaya in Dharmasraya District, one of the KUDs who wishes to apply replanting to farmer groups whose members,t found some obstacles in the implementation. This activity aims to facilitate KUD Bukit Jaya in order to realize the replanting activities in its working area. This action research is conducted using four stages of approach, namely: [1] introduction of problems with dialogical approaches, using interview techniques and discussions with cooperative managers as well as farmers whose gardens have to implement replanting; [2] the team analyzes the problems found and contacts the parties related to issues conveyed by cooperatives and farmers; the parties are insurance companies, bappeda as coordinator of cooperative technical service; [3] holding discussions and discussions with the cooperation, farmer groups and involved parties (insurance companies, cooperative agencies, and district government); [4] agreed on assistance for the preparation of cooperative and peasant group work plans for the preparation and implementation of replanting